2014
DOI: 10.1093/infdis/jiu273
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Bioenergetics and Acute Mitochondrial Dysfunction: A Clue to Understanding the Central Nervous System Side Effects of Efavirenz

Abstract: Efavirenz affects the bioenergetics of neurons through a mechanism involving acute mitochondrial inhibition, an action exacerbated in neuroinflammatory conditions. A similar scenario of glial cells survival and degeneration of neurons with signs of mitochondrial dysfunction and oxidative stress has been associated with neurocognitive disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
60
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 40 publications
9
60
0
Order By: Relevance
“…Several other studies have provided direct evidence that antiretroviral drugs can exert neurotoxic effects in connection with oxidative stress, dysregulation of Ca 2ϩ homeostasis, and alteration of mitochondrial respiration (14,17,62,(73)(74)(75)(76)(77)(78). Furthermore, similar to HIV-1 gp120, the earliest antiretroviral drug, AZT, has been shown to impair neurogenesis (79-81), besides affecting cerebrocortical mitochondria (82).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several other studies have provided direct evidence that antiretroviral drugs can exert neurotoxic effects in connection with oxidative stress, dysregulation of Ca 2ϩ homeostasis, and alteration of mitochondrial respiration (14,17,62,(73)(74)(75)(76)(77)(78). Furthermore, similar to HIV-1 gp120, the earliest antiretroviral drug, AZT, has been shown to impair neurogenesis (79-81), besides affecting cerebrocortical mitochondria (82).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, similar to HIV-1 gp120, the earliest antiretroviral drug, AZT, has been shown to impair neurogenesis (79-81), besides affecting cerebrocortical mitochondria (82). Efavirenz (EFV) and NVP, which are currently FDA approved and used in NNRTI regimens (http://aidsinfo.nih.gov/guidelines), have been suggested to exert neurotoxicity (14,62,83). One study found that EFV caused a loss of ATP, depolarization and fragmentation of mitochondria, and increased mitophagy and autophagy, in general, in neuron-like SHSY-5Y cells and primary rat striatal neurons, suggesting a disturbance of energy homeostasis as a mechanism of toxicity (84).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…EFV also inhibits mitochondrial complex IV activity in mice (Streck et al, 2011). The bioenergetic effects of EFV in neurons have recently been demonstrated (Funes et al, 2014). Because of the critical role that autophagy plays in postmitotic cells, such as neurons (Nixon, 2013), we sought to determine the effect of EFV on neuronal autophagy.…”
Section: Introductionmentioning
confidence: 99%